A key role for tetrahydrobiopterin-dependent endothelial NOS regulation in vascular resistance arteries: studies in endothelial cell tetrahydrobiopterin-deficient mice - Chuaiphichai, S; Crabtree, M; McNeill, E; Hale, A; Trelfa, L; Channon, K; Douglas, G (John Wiley & Sons Ltd, 2017)
Background and purpose: The cofactor tetrahydrobiopterin (BH4) is a critical regulator of endothelial NOS (eNOS) function, eNOS-derived NO and reactive oxygen species (ROS) signalling in vascular physiology. To determine the physiological requirement for de-novo endothelial cell BH4 synthesis in vasomotor function in resistance arteries, we have generated a mouse model with endothelial cell-specific deletion of Gch1, encoding GTP cyclohydrolase 1 (GTPCH), an essential enzyme for BH4 biosynthesis, and evaluated BH4-dependent eNOS regulation, eNOS-derived NO and ROS generation. Experimental approach: Wire myography was used to assess the reactivity of mouse 2nd order mesenteric arteries. High-performance liquid chromatography was used to determine BH4, BH2 and biopterin. Western blotting was used for expression analysis. Key Results: Gch1fl/flTie2cre mice demonstrated reduced GTPCH protein and BH4 levels in mesenteric arteries. Deficiency in endothelial cell BH4 leads to eNOS uncoupling, increased ROS production and loss of NO generation in mesenteric arteries of Gch1fl/flTie2cre mice. Gch1fl/flTie2cre mesenteric arteries had enhanced vasoconstriction to U46619 and phenylephrine, which was equalised by L-NAME. Endothelium-dependent vasodilatations to ACh and SLIGRL were impaired in mesenteric arteries from Gch1fl/flTie2cre mice compared to wild-type littermates. The loss of eNOS-derived NO-mediated vasodilatation was associated with increased eNOS-derived H2O2 and prostaglandin-derived vasodilator in Gch1fl/flTie2cre mesenteric arteries. Conclusions and implications: Endothelial cell Gch1 and BH4-dependent eNOS regulation play pivotal roles in maintaining vascular homeostasis in resistance arteries. Therefore, targeting vascular Gch1 and BH4 biosynthesis may provide a novel therapeutic target for the prevention and treatment of microvascular dysfunction in patients with cardiovascular disease.